The fire in fiction : passion, purpose, and techniques to make your novel great - Maass, Donald, ....- (Cincinnati (Ohio) : Writer's digest books, 2009)
In The fire in fiction, successful literary agent and author Donald Maass shows you not only how to infuse your story with deep conviction and fiery passion, but how to do it over and over again. The book features: techniques for capturing a special time and place, creating characters whose lives matter, nailing multiple-impact plot turns, making the supernatural real, infusing issues into fiction, and more. Story-enriching excercises at the end of every chapter to show you how to apply the practical tools just covered to your own work. Rich examples drawn from contemporary novels as diverse as The Lake House, Water for Elephants, and Jennifer Government to illustrate how various techniques work in actual stories. Plus, Maass introduces an original technique that any novelist can use any time, in any scene, in any novel, even on the most uninspired day... tot take the most powerful experiences from your personal life and turn those experiences directly into powerful fiction.
Keywords: Writing